2017
DOI: 10.1177/0165025417738057
|View full text |Cite
|
Sign up to set email alerts
|

An after-school intervention targeting executive function and visuospatial skills also improves classroom behavior

Abstract: Executive function (EF) describes a complex set of skills, including flexible attention, inhibitory control, and working memory, that coordinate to achieve behavioral regulation. Visuospatial skills (VS) describe the capacity to visually perceive and understand spatial relationships among objects. Emerging research suggests VS skills are associated with classroom functioning, including behavioral adjustment. Children from socioeconomically disadvantaged backgrounds are more likely to enter school with EF and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Studies on the effectiveness of handwriting intervention programs found improvements in fine motor and visual-motor skills in children receiving direct occupational therapy lasting seven or more months [33][34][35][36]. Nevertheless, research has suggested that even short-term interventions targeting fine motor performances in children of lower elementary school ages can lead to significant changes in individuals with or without disabilities [37][38][39][40][41][42].…”
Section: Intervention Programs Duration and Gender Differencesmentioning
confidence: 99%
“…Studies on the effectiveness of handwriting intervention programs found improvements in fine motor and visual-motor skills in children receiving direct occupational therapy lasting seven or more months [33][34][35][36]. Nevertheless, research has suggested that even short-term interventions targeting fine motor performances in children of lower elementary school ages can lead to significant changes in individuals with or without disabilities [37][38][39][40][41][42].…”
Section: Intervention Programs Duration and Gender Differencesmentioning
confidence: 99%
“…Non-language-based training was also shown to be highly beneficial with special school age groups such as students with Down Syndrome, autism, ADHD, and others, showing significant and sustained improvement in academic skills (Bennett et al, 2013;Brock et al, 2018). Connections were also made between executive function skills, VS skills and school achievement, especially in at-risk populations.…”
Section: Shifting the Landscape: Effects And Benefits Of Training Nlbmentioning
confidence: 99%
“…Kindergarten-aged children, or children about ages five or six, are also an important population to discuss in and of themselves, as they are developmentally unique. First, because executive function is closely linked to emergent literacy and math skills (Brock et al, 2018a;Brock et al, 2018b), differences in executive function skills translates into differing levels of school readiness (Cuevas & Bell, 2014;Huber, Yeates, Meyer, Fleckhammer, & Kaufman, 2018;Nathanson et al, 2014;Wagner Fuhs & Day, 2011). As such, as children enter kindergarten, they present with a multitude of variances in executive function skills, thus school readiness.…”
Section: Kindergarten-aged Childrenmentioning
confidence: 99%
“…Interactive screen time in which the user interacts with the interface can potentially increase children's number sense, basic math skills, and even problem solving and geometric skills (Lieberman, Bates, & So, 2009). Additionally, further emergent research has indicated that Visuomotor Integration (VMI), or a child's ability to comprehend and manipulate visual input, including letters and numbers and hands-on learning materials, paired with executive function, are important in developing children's reading and math skills (Brock et al, 2018a;Brock et al, 2018b).…”
mentioning
confidence: 99%